2022
DOI: 10.1002/anie.202212634
|View full text |Cite
|
Sign up to set email alerts
|

Host Spin‐Crossover Thermodynamics Indicate Guest Fit

Abstract: Spin-crossover (SCO) metal-organic cages capable of switching between high-spin and low-spin states have the potential to be used as magnetic sensors and switches. Variation of the donor strength of heterocyclic aldehyde subcomponents in imine-based ligands can tune the ligand field for a Fe II center, which results in both homoleptic and heteroleptic cages with diverse SCO behaviors. The tetrahedral SCO cage built from 1-methyl-1H-imidazole-2-carbaldehyde is capable of encapsulating various guests, which stab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 118 publications
0
20
0
Order By: Relevance
“…36 It also enriches the function of cages and extends their potential applications for molecular switches and optical sensors. 37−42 Nevertheless, the preparation of SCO cages to date is limited to the use of Fe II with azole-based ligands, [29][30][31][32][33]36 which afford appropriate ligand fields for SCO. The exploration of new approaches to construct SCO cages and to control SCO behaviors remains challenging.…”
Section: ■ Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…36 It also enriches the function of cages and extends their potential applications for molecular switches and optical sensors. 37−42 Nevertheless, the preparation of SCO cages to date is limited to the use of Fe II with azole-based ligands, [29][30][31][32][33]36 which afford appropriate ligand fields for SCO. The exploration of new approaches to construct SCO cages and to control SCO behaviors remains challenging.…”
Section: ■ Introductionmentioning
confidence: 95%
“…They have proven useful in a range of applications, including molecular recognition, stereochemical sensing, , chemical separation, stabilization of reactive species, and catalysis. In particular, the construction of spin-crossover (SCO) coordination cages, of which the metal centers are capable of switching between high-spin and low-spin states upon external stimuli, have received a growing interest. The magnetic switching of cages accompanied by the length variations of coordination bonds provides a new means to modulate the cavity volumes and therefore the guest binding properties . It also enriches the function of cages and extends their potential applications for molecular switches and optical sensors. Nevertheless, the preparation of SCO cages to date is limited to the use of Fe II with azole-based ligands, , which afford appropriate ligand fields for SCO.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,28 Halcrow's systematic solution study on 2,6-di(pyrazol-1-yl)pyridine-based complexes revealed that electron-donating p-pyridine substituents lower T 1/2 while m-pyrazole substituents raise it, 18 attributed to differing σ and π bonding contributions. 18,28 Spin-crossover cages [29][30][31][32][33][34][35][36][37][38][39] consist of multiple Fe II ions and organic ligands with two or more coordination motifs connected via linkers. They are an interesting emerging class of spin-crossover materials 2,3 since multiple avenues exist for tuning the spincrossover properties.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] An interesting case of host functionality results from the presence of Fe 2+ centres with spin crossover (SCO) switching properties. [8][9][10][11][12][13][14] Of the latter, most of the reported instances involve tetrahedral Fe 4 or cubic Fe 8 cages. 10,12,13,15,16 However, much simpler hosts involving only two iron centers are rarely found encapsulating any species.…”
mentioning
confidence: 99%